Hopping or Jumping on the Cliffs: The Unusual Phylogeographical and Demographic Structure of an Extremely Narrow Endemic Mediterranean Plant - Strumia, Sandro; Santangelo, Annalisa; Galise, Teresa Rosa; Cozzolino, Salvatore; Cafasso, Donata (Frontiers in Plant Science, 2021)
Several past and recent climatic and geological events, have greatly influenced the current distribution of paleoendemic coastal species around the Mediterranean Basin, rendering complex the reconstruction of their distributional history. In this study we used both chloroplast and nuclear SNPs to assess the levels of genetic differentiation, contemporary/historical levels of gene flow and demographic history for the three only known (one mainland and two insular) populations of Eokochia saxicola, a rare Mediterranean palaeoendemic coastal rocky halophyte. Plastid genome analysis revealed very low intraspecific haplotype variation and partial admixture among Capri and Palinuro populations with at least two independent colonization events for the Strombolicchio islet. Nuclear SNPs variation consistently identified three distinct genetic clusters corresponding to our sampling localities. Furthermore, strong genetic isolation was confirmed by both historical and contemporary levels of migration among the three populations. The DIYABC analysis identified two introductions temporally separated from Palinuro to Capri (ca. 0.25 Mya) and subsequently to Strombolicchio (ca. 0.09 Mya) as the most likely hypothesis for the current distribution of E. saxicola. Regardless of their small population sizes, all study sites supported high genetic diversity maintained by outcrossing and random mating between individuals owing largely from wind pollination, an exclusive trait among Mediterranean narrow endemics. In conclusion, the patterns observed confirm that Mediterranean endemics are not necessarily “evolutionary dead-ends,” but rather represent species that have an extensive demographic stability and a strong evolutionary legacy.